2020
DOI: 10.1002/bjs.11854
|View full text |Cite
|
Sign up to set email alerts
|

International variation in managing locally advanced or recurrent rectal cancer: prospective benchmark analysis

Abstract: Background: Tumour extension beyond the mesorectal plane (ymrT4) occurs in 5-10 per cent of patients with rectal cancer and 10 per cent of patients develop locally recurrent rectal cancer (LRRC) after primary surgery. There is global variation in healthcare delivery for these conditions. Methods: An international benchmark trial of the management of ymrT4 tumours and LRRC was undertaken in France and Australia between 2015 and 2017. Heterogeneity in management and operative decision-making were analysed by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 21 publications
2
42
0
Order By: Relevance
“…One study was conducted in both Australia and France [20]. Seven studies reported financial support, all provided by the local government or governmental organizations [1,6,10,20–23]. Studies included data on 878 patients.…”
Section: Resultsmentioning
confidence: 99%
“…One study was conducted in both Australia and France [20]. Seven studies reported financial support, all provided by the local government or governmental organizations [1,6,10,20–23]. Studies included data on 878 patients.…”
Section: Resultsmentioning
confidence: 99%
“…Our literature review and meta-analysis showed the necessity to fill the vacuum left by APR to reduce major perineal wound complications. This observation is more difficult to assert for more extensive resections, which are most often for more specialized and less standardized indications such as recurrence of pelvic cancer [4] or rarer neoplasia such as sarcomas. For this reason, we have endeavored to separate the studies of pelvic exenterations, on the one hand, and to standardize the classification of complication outcomes with the Southampton Wound Complication Scale complications, on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, this specialized center surgery often requires a multidisciplinary team including plastic and pelvic surgeons [39]. This surgery is intended for patients with a long oncological history who have received numerous courses of chemotherapy and often even re-irradiation for pelvic recurrences [4]. Our meta-analysis shows a significant increase in total perineal complications in case of closure with the VRAM flap (OR 2.46, 95% CI 1.39-4.35; p < 0.01; I 2 = 46%) This result is found for major complications, but it was not significant (OR 1.67, 95% CI 0.90-3.08; p = 0.1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, abdominal surgery has made progress to date with minimally invasive surgery and early rehabilitation protocols. However, recent progress in oncology now allows the tumour or tumour recurrence to be managed at advanced stages through often extensive surgery (Denost et al, 2020). These increasingly frequent treatments, such as cytoreductive surgery for peritoneal carcinomatosis or pelvic recurrence, for example, are a source of POI.…”
Section: Discussionmentioning
confidence: 99%